Efficacy of Beauveria bassiana against adults of Prostephanus truncatus (Horn), Sitophilus zeamais Motschulsky and Teretrius nigrescens Lewis in stored maize - Acheampong, Mavis Agyeiwaa; Cornelius, Eric William; Eziah, Vincent Yao; Fening, Ken Okwae; Ofori, Kwadwo; Storm, Claire; Jessop, Nick; Luke, Belinda; Moore, David; Clottey, Victor Attuquaye; Potin, Olivier; Grammare, Pierre (African Entomology, 2023)
The larger grain borer, Prostephanus truncatus (Horn) and the maize weevil, Sitophilus zeamais Motschulsky continue to cause tremendous losses to stored maize. Research in the UK has identified Beauveria bassiana, IMI 389521 as a suitable control agent for grain storage pests in the UK. The pathogenicity of B. bassiana, IMI 389521 was evaluated against adult P. truncatus, S. zeamais and Teretrius nigrescens in Ghana. Fifty adults of each insect species were treated with 0.5 g dry conidia powder of this isolate at 8.65 × 108 conidia/g for 1 minute and mortality recorded daily for 14 days. The results indicated that B. bassiana, is pathogenic against P. truncatus and S. zeamais, inducing over 90% mortality by day 7. Teretrius nigrescens was, however less susceptible to the fungus with 30% mortality. To determine the most effective concentration of B. bassiana for the control of P. truncatus, a laboratory dose response experiment using four concentrations of B. bassiana (108–1011 cfu/kg maize) was also conducted. Maize grains (250 g) in separate jars were treated with the four concentrations of the product. Fifty adults of P. truncatus were placed into the jars containing the treated maize and mortality was assessed weekly for 3 weeks. The most effective dose was 1010 cfu/kg maize, which resulted in 96% and 100% mortality of P. truncatus after 2 and 3 weeks, respectively. This study shows that B. bassiana could effectively be integrated into bio-control programme of these two key pests of maize in Ghana after further field trials.